AFRICA'S FOREIGN POLICY AND NATION BRANDING: REGIONAL LEADERSHIP AND ITS DISCONTENTS (The Strategic Review for Southern Africa, 2021)
Whether they know it or not, countries are viewed through the lens of branding. Their brand equity lies in the norms and ideas that they project, as well as the actors (leaders) who champion such ideas and norms. Countries embody signs, beliefs, values, and imageries about what they stand for in the global system, and it is this that has an effectupon the imagery and preferences of others rather than merely marketing techniques. As such, countries carry — or project — a 'persona' that expresses their identity, ideas, values, and norms.This article focuses on the regional dimensions of South Africa's brand value and leadership. This is precisely because regions are crucial platforms through which countries project their ideas, norms, and leadership. It is also here that they build their brand equity. As such, this article examines the kinds of norms that South Africa projects through the region, and understands how these are perceived. Further, it analyses the predominant ideas that South Africa articulates.